Analysis of the time-velocity curve in phase-contrast magnetic resonance imaging: a phantom study. (7th October 2019) - Park, Jieun; Kim, Junghun; Chang, Yongmin; Youn, Sung Won; Lee, Hui Joong; Kang, Eun-Ju; Lee, Ki-Nam; Suchánek, Vojtěch; Hyun, Sinjae; Lee, Jongmin
Abstract: The aim of this study was to analyze the characteristics of time-velocity curve acquired by phase-contrast magnetic resonance imaging (PC-MRI) using an in-vitro flow model as a reference for hemodynamic studies. The time- velocity curves of the PC-MRI were compared with Doppler ultrasonography (US) and also compared with those obtained in the electromagnetic flowmeter. The correlation between techniques was analyzed using an electromagnetic flowmeter as a reference standard; the maximum, minimum, and average velocities, full-width at half-maximum (FWHM), and ascending gradient (AG) were measured from time-velocity curves. The correlations between an electromagnetic flowmeter and the respective measurement technique for the PC-MRI and Doppler US were found to be high (mean R 2  > 0.9, p  < 0.05). These results indicate that these measurement techniques are useful for measuring blood flow information and reflect actual flow. The PC-MRI was the best fit for the minimum velocity and FWHM, and the maximum velocity and AG were the best fit for Doppler US. The PC-MRI showed lower maximum velocity value and higher minimum velocity value than Doppler US. Therefore, PC-MRI demonstrates more obtuse time-velocity curve than Doppler US. In addition, the time- velocity curve of PC-MRI could be calibrated by introducing formulae that can convert each measurement value to a reference standard value within a 10% error. The PC-MRI can be used to estimate the Doppler US using this formula.